2016
DOI: 10.1177/0042085916651320
|View full text |Cite
|
Sign up to set email alerts
|

“It’s All Possible”: Urban Educators’ Perspectives on Creating a Culturally Relevant, Schoolwide, College-Going Culture for Black and Latino Male Students

Abstract: This article examines how 18 teachers, counselors, administrators, and support staff from seven New York City public high schools collaborated during the Black and Latino Male Professional Development Initiative (a pseudonym) to develop a "culturally relevant, schoolwide, college-going culture" supportive of Black and Latino males' college readiness and access. We draw from a mixed-methods empirical research study to discuss participants' changing understandings of the features of such a culture, and how parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Too many of the K-12 students we taught, particularly Black and Latino male students in NYC, were pushed out of school before earning a high school diploma, and some who did graduate struggled to surmount barriers created by under-preparedness and miseducation (see Woodson, 2008). Those who persisted were often encouraged by educators of color who supported them socially, emotionally, and academically despite structural barriers that could have otherwise deterred their progress (Knight-Manuel et al, 2016). Our experiences educating pre- and inservice teachers in NYC, more precisely the challenges we have faced in so doing, further situate our personal and intellectual commitments to preparing educators to improve educational outcomes and experiences for Black and Latino males.…”
Section: Introductionmentioning
confidence: 99%
“…Too many of the K-12 students we taught, particularly Black and Latino male students in NYC, were pushed out of school before earning a high school diploma, and some who did graduate struggled to surmount barriers created by under-preparedness and miseducation (see Woodson, 2008). Those who persisted were often encouraged by educators of color who supported them socially, emotionally, and academically despite structural barriers that could have otherwise deterred their progress (Knight-Manuel et al, 2016). Our experiences educating pre- and inservice teachers in NYC, more precisely the challenges we have faced in so doing, further situate our personal and intellectual commitments to preparing educators to improve educational outcomes and experiences for Black and Latino males.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of this debt are profound: For example, analysis of 5 million high school graduates in 2016 found that 54% of students from lower income schools entered college compared with 69% of students from higher income backgrounds (National Student Clearinghouse, 2016).To address these disparities in the college admissions experience, both a short-term and a longer term strategy directly linked to the college admissions essay-writing process are arguably vital. In the shorter term, providing students with instruction on meeting challenges they face in writing admissions essays may help them navigate the larger college admissions process (Knight-Manuel et al, 2016;Wight, 2017). In the longer term, those concerned with social justice must push back at a systemic level against gatekeeping practices associated with class differences that stand in the way of college access for all who want to attend college.…”
mentioning
confidence: 99%
“…To bring the students to The College would be a great field trip not just for science learning but to introduce them to a college campus, starting the college-going mind-set early (Knight-Manuel et al, 2016). Michele expressed, “I’m excited and hoping to bring the kids—now, look at me, my hopes and dreams, to bring them to [The College] for a [science] lab as a field trip.” Michele mentioned to one White colleague about her class and the other first-grade class (taught by another Teachers of Color Study participant) going to The College to take science classes:“You have such a good asset.…”
Section: Resultsmentioning
confidence: 99%